Immersive Virtual Reality-Based Distraction in Post-Surgical Pain and Anxiety Management: A Systematic Review - Susi Dwi Utarti; Masfuri Masfuri; Liya Arista; Sri Yona (Media Publikasi Cendekia Indonesia, 2026)
The effective management of postoperative pain and anxiety remains a challenge in patient care. Immersive virtual reality (IVR)-based distraction has been proposed as a non-pharmacological intervention to help reduce these symptoms. This study aimed to evaluate the effectiveness of immersive VR-based distraction in reducing postoperative pain and anxiety. This systematic review followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines by identifying studies that assessed immersive VR-based distraction in postoperative patients. Studies published from 2015 to 2025 were searched in ClinicalKey Nursing, EbscoHost, ProQuest, ScienceDirect, Scopus, and Taylor and Francis databases. Fourteen randomized controlled trials (RCTs) were included, covering various surgical contexts such as orthopedic, abdominal, cardiac, and oral surgery. Most studies showed that immersive VR-based distraction effectively reduced postoperative pain and anxiety, although some reported no significant effect. Variations in outcomes were influenced by patient characteristics, duration and frequency of VR use, and the type of VR content. Studies were excluded if they involved non-postoperative populations, pediatric samples, non-immersive VR, or non-interventional designs. Overall, immersive VR-based distraction shows promise in reducing postoperative pain and anxiety, although variability in effectiveness highlights the need for further research on technical parameters and clinical implementation